2021
DOI: 10.3390/en14196153
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Boundary Method for Design Consideration of Resonant DC-DC Converters

Abstract: The paper presents a new unified method for designing the two basic types of serial resonant DC-DC converters (series and with a parallel-loaded capacitor). The method is based on the use of a simplified generalized approach for the analysis of this type of power electronic devices. It is characterized by the fact that regardless of the specific operating mode, with a control frequency below or above the resonant of the series resonant circuit to determine the relationship between input and output voltage or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The series RLC circuit under consideration is described by the following differential equation with respect to the capacitor voltage [16,22]:…”
Section: Analysis Of a Resonant Dc/ac Converter With Reverse Diodesmentioning
confidence: 99%
See 2 more Smart Citations
“…The series RLC circuit under consideration is described by the following differential equation with respect to the capacitor voltage [16,22]:…”
Section: Analysis Of a Resonant Dc/ac Converter With Reverse Diodesmentioning
confidence: 99%
“…It is formed by the sequential operation of the semiconductor switches (transistors and reverse diodes) of the inverter with a switching frequency f = 1/T. When operating in an established mode and fulfilling the condition for resonance-R < 2 L C the following expressions of the current through the inductance and the voltage of the capacitor are valid for the circuit under consideration [22,25,26]:…”
Section: Analysis Of a Resonant Dc/ac Converter With Reverse Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The time diagrams presented in Figure 4 provide an opportunity to evaluate the deviations of the real form of the current in the AC circuit with that of operation in the border mode (ν =1). From them, it is found that the differences are insignificant and do not significantly affect the design accuracy [32].…”
Section: Transfer Function Of a Resonant Inverter With Reverse Diodes...mentioning
confidence: 99%
“…The first mentioned refers to an electrical limit (such as a transformer) amid the inputs and outputs which allows the usage for high voltages. Examples of these types are flyback, forward, resonant, push-pull and bridge [16][17][18][19][20]. In the non-isolated, the configuration indicates that the mentioned barrier is vanished and therefore, the efficiency tends to be higher since the number of components is lower [21].…”
Section: Introductionmentioning
confidence: 99%